The Effectiveness of Integrating Virtual Reality and Didactic Games in Physiological Education - Farkhodovna, Salimova Sarvinoz; Odilovna, Komilova Bakhmal; Amonovich, Shamsiyev Naim (Universitas Muhammadiyah Surakarta, 2025)
Teaching complex topics such as homeostatic and pathophysiological processes in physiology often presents difficulties with traditional approaches. The aim of this study was to assess the impact of complex integration of virtual reality (VR) simulators and didactic games on the effectiveness of physiology education. The research was conducted with 920 biology students from four pedagogical institutes in Uzbekistan (Shahrisabz, Urgench, Namangan, Nukus). The experimental group (n=460) was taught using VR simulators such as